6.9k views
2 votes
The steps to derive the quadratic formula are shown below:

Step 1 ax2 + bx + c = 0
Step 2 ax2 + bx = − c
Step 3

Provide the next step to derive the quadratic formula.

A. a times the quantity x squared plus b over a times x end quantity equals negative c
B. x(ax + b) = −c
C. x squared over a plus b over a times x equals negative c over a
D. x squared over a plus b over a equals negative c over a

1 Answer

6 votes

Answer:

A. a times the quantity x squared plus b over a times x end quantity equals negative c

Explanation:

ax^2 + bx + c = 0

Subtract c from each side

ax^2 + bx+c-c =0 − c

ax^2 + bx = − c

Now we factor out an a

a(x^2 +b/a) = -c

User Matthew Fioravante
by
5.1k points